Implementasi Penyelenggaraan Administrasi Kependudukan pada Warga Non-Permanen dalam Memitigasi Urbanisasi di Kota Surabaya - Ragil Putri Pinaring Gusty (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
The state’s efforts to provide accurate and up-to-date population data for various development needs, such as planning policies and public services, are known as the implementation of population administration. Due to the large number of people living in big cities, many non-permanent residents have not been officially registered. This is due to difficult procedures, lack of legal knowledge, and limited access to population registration services. The need to maintain the basic rights of every citizen, both permanent and non-permanent, and ensure orderly administration as part of national development is the basis of the policies used to manage population administration. By ensuring proper data collection, accurate recording, and legal protection for non-permanent residents, proper population administration is expected to be an important tool to reduce the negative impacts of urbanization, especially in the city of Surabaya. This study aims to determine how population administration for non-permanent residents in the city of Surabaya is implemented in the context of urbanization and to suggest more reasonable and efficient policies. The results of the study, which was conducted using a qualitative approach by conducting literature research, in-depth interviews, and policy analysis, showed that simplifying registration procedures, increasing socialization, and increasing cooperation between related institutions are needed to carry out population administration for non-permanent residents.